Nurses' Knowledge Concerning End of Life Care in Critical Care Units - Shehab Ahmed Hamid, Tahseen R. Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
The study aimed to assess nurses' Knowledge toward Palliative Care of Patients end of life phase, a descriptive cross-sectional study design is carried out from the period of November 2021) to (1th February 2022). A probability simple random sampling technique Then, the number of participants in each selected hospital were determined using the sampling to each randomly selected at hospital in Dyala city in Iraq. A total of (100) nurses were working in the critical care units during the time of the study period and met the study criteria and agree to participate. Ten nurses for pilot study were excluded from the study. the result of co-relation co efficient were (79%). Study data were collected through A questionnaire was built as a data collection tool and consisted of two parts instrument. The study found results of this study showed that nurses are good knowledge (74.0%) for palliative care and toward End of life care among nurses working in Dyala city in Iraq. This study emphasizes the need to develop palliative care services. The study recommends Education or training the nurses who read the articles about palliative care. Provide evidence More attention and resources should be directed towards education and support Nurses who care for patients with palliative care needs.